Pengaruh Variasi Kondisi Operasi pada Kolom Distilasi Ekstraktif terhadap Sifat Fisis Pelarut Hidrokarbon Terdearomatisasi - Prasetiawan , Haniif; Rengga, Wara Dyah Pita; Fardhyanti , Dewi Selvia; Triwibowo , Bayu; Chafidz, Achmad (Politeknik ATI Padang, 2022)
Solvent is one of the important components in chemical processes. The type of solvent that is often used in the paint and coating industry is a hydrocarbon-based solvent which consists of a diverse complex mixture of liquids and contains aliphatic, alicyclic and aromatic (C5-C8) elements. Aromatic hydrocarbons are environmental pollutants that are known to be toxic, carcinogenic and mutagenic, so a hydrocarbon-based solvent with an aromatic content of less than 1% is needed. An appropriate separation method for separating aromatic and nonaromatic components having close boiling points is extractive distillation with a sulfolane entrainer. In this study, a distillation system with a sulfolane entrainer was run using the process simulation software Aspen Plus with the aim of understanding the effect of the amount of sulfolane, feed stage and number of stages on the physical properties of hydrocarbon-based solvents. This simulation is focused on the variation of the ratio of sulfolane: crude feed (7:1, 7.5:1, 8:1, 8.5:1), the variation of the feed stage (10th stage to the 35th stage) and the variation of the number of stages (70, 75, 80). It was found that the number of stages did not affect the density and flash point of the solvent. An increase of number of stage will decrease the solvent flash point and density. Significant decreament also can be found when the sulfolane to crude feed ratio is increased. However, the physical properties of the current dearomatized solvent is close to the properties of commercial product namely SBP 65/70 from one of oil and gas companies.